The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.16970/ted.62135
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivities of cry gene positive Bacillus thuringiensis (Berliner) (Bacillales: Bacillaceae) strains on Ephestia kuehniella Zeller, 1879 and Plodia interpunctella (Hübner, 1813) (Lepidoptera: Pyralidae)

Abstract: Bioactivities of cry gene positive Bacillus thuringiensis (Berliner) (Bacillales: Bacillaceae) strains on Ephestia kuehniella Zeller, 1879 and Plodia interpunctella (Hübner, 1813) (Lepidoptera: Pyralidae) 1,2 cry gene pozitif Bacillus thuringiensis (Berliner) (Bacillales: Bacillaceae) izolatlarının

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
4
1
Order By: Relevance
“…The highest mortality for E. kuehniella happened by the Tunisia isolate, BLB1, harboring cry1 and cry2 in comparison with Btk HD1 (Saadaoui et al, 2010). In comparison with the current bioassay result, some Turkish Bt strains harboring cry2Ab and cry2Aa1 led to 42% mortality in E. kuehniella (higher than Btk) (Alper et al, 2016).…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…The highest mortality for E. kuehniella happened by the Tunisia isolate, BLB1, harboring cry1 and cry2 in comparison with Btk HD1 (Saadaoui et al, 2010). In comparison with the current bioassay result, some Turkish Bt strains harboring cry2Ab and cry2Aa1 led to 42% mortality in E. kuehniella (higher than Btk) (Alper et al, 2016).…”
Section: Discussioncontrasting
confidence: 44%
“…A previous investigation revealed that molecular mass of Cry1Aa, Cry1Ac, and Cry1C proteins were 133.2, 133.3, and 134.8 kDa analyzed through the SDS-PAGE, respectively (Kalman et al, 1995). All strains studied by Alper et al (2016), harboring the cry1 and cry2 genes, and the reference strain, Btk, almost revealed similar crystal protein contents. Similar results have been achieved for the most Iranian strains studied in the present research.…”
Section: Discussionmentioning
confidence: 78%
“…So far a large number of Bt strains have been isolated and characterized for their sequence similarities within these cry genes. A total of 700 cry genes have been isolated till date (Alper et al 2016) and interestingly, single strains of Bt may contain more than one crystal protein genes (Letowski et al 2005;Pedro and Ibarra 2010). Although there are variations within the cry genes, the three domain of Cry proteins have conserved domains in their tertiary structures of the active toxin.…”
Section: Introductionmentioning
confidence: 99%
“…The researchers concluded that this was due to the decrease in the number of eggs laid by females in plants sprayed with Dipel. In another study, Alper et al (2013), in their study examining the effect of a spore-crystal mixture of 31 natural B. thuringiensis isolates on T. urticae nymphs, noted that some isolates may have a certain potential in the development of biopesticides that especially retard the growth of nymphs. Moreover, Neethu et al (2016), stated that toxin-producing bacteria such as B. thuringiensis have been widely used as bio-acaricide in recent years.…”
Section: Resultsmentioning
confidence: 99%